When Not Following Procedures Is a Safer Way: A Study on Selective Intentional Non-Compliance - Ankersø,Daniel; Nielsen,Søren (2025)
This study investigates the concept of Selective Intentional Non-Compliance (SINC) in aviation. Deliberate, context-driven deviations from procedures motivated by safety in response to dynamic operational conditions. Based on a survey of 39 European commercial pilots, we analysed the prevalence, motivations, and perceived outcomes of procedural deviations. Nearly 43% reported deviating from standard operating procedures (SOPs) occasionally or frequently in the past year. Of these, 29% indicated safety as the primary reason. The study found that rigid adherence to SOPs is not always perceived as the safest course of action and that well-judged deviations may enhance safety in complex operational scenarios. The findings also revealed underreporting of such deviations, likely due to fear of reprisal or normalization of success-driven deviations. The research supports the view that adaptive decision-making based on situational awareness is a critical safety asset. SINC appears to be a real, underrecognized behaviour that, when properly understood and supported, could inform procedural design and pilot training. The study highlights the need to reframe non-compliance in safety management systems and training to reflect the nuanced realities of dynamic flight operations.
Keywords: Aviation Safety; Selective Intentional Non-Compliance (SINC); Human Factors; Procedure Compliance; Pilot Behaviour; FLYL01